Mother's Knowledge of Breastfeeding and Nutrition as a Prevention of Stunting Children: Pengetahuan Ibu Mengenai ASI dan Gizi Sebagai Upaya Pencegahan Anak Stunting - Mubyaring Putri Sayekti, Azzahra; Purwaningsih, Endang; Perdana, Putra (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Stunting has become a world concern that is a nutritional problem, mainly in middle-income countries. According to the World Health Organization (WHO), stunting is a condition caused by recurrent infections, psychosocial simulations, and most obviously by malnutrition. With the prevalence of stunting news at 27.4% in 2021, attention is needed as an effort to reduce the figure in the district of Mojokerto. MBKM Village Free Stunting as a community dedication aims to improve public understanding and knowledge about the health of pregnant mothers, breastfeeding, weaning food, and nutritional competence in the framework of stunting prevention. With the method of socialization attended by 40 mothers from the village of Bandarasri, there was a 14% improvement in understanding about the health of pregnant mothers, 36% about breastfeeding and MP-ASI, 34% about nutritional properties in infants, and 57% about stunting. Based on the presentation, it was shown that socialization activities had an impact on stunting prevention efforts in Bandarasri Village, Ngoro Prefecture, Mojokerto District, East Java.